2006
DOI: 10.1029/170gm19
|View full text |Cite
|
Sign up to set email alerts
|

How thick is a fault? Fault displacement-thickness scaling revisited

Abstract: Fault zone thickness is an important parameter for many seismological models. We present three new fault thickness datasets from different tectonic settings and host rock types. Individual fault zone components (i.e., principal slip zones, fault core, damage zone) display distinct displacement-thickness scaling relationships. Fault component thickness is dependent on the type of deformation elements (e.g., open fractures, gouge, breccia) that accommodate strain, the host lithology, and the geometry of pre-exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
94
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 32 publications
6
94
0
1
Order By: Relevance
“…The functional form of the decrease in structure density is similar to models for decreasing stress magnitudes with distance from a fault [Cowie and Scholz, 1992;Scholz et al, 1993;Savage and Brodsky, 2011]. However, the rate of decrease in structure density and damage zone thickness vary significantly for different faults, contributing to scattered scaling relations between damage zone characteristics and displacement [e.g., Hull, 1988;Evans, 1990;Knott et al, 1996;Shipton et al, 2006;Childs et al, 2009;Faulkner et al, 2011a;Savage and Brodsky, 2011]. Damage zone thickness may also scale with parent fault length [Vermilye and Scholz, 1998;Davatzes and Aydin, 2003;de Joussineau et al, 2007;Perrin et al, 2016].…”
Section: Introductionmentioning
confidence: 98%
“…The functional form of the decrease in structure density is similar to models for decreasing stress magnitudes with distance from a fault [Cowie and Scholz, 1992;Scholz et al, 1993;Savage and Brodsky, 2011]. However, the rate of decrease in structure density and damage zone thickness vary significantly for different faults, contributing to scattered scaling relations between damage zone characteristics and displacement [e.g., Hull, 1988;Evans, 1990;Knott et al, 1996;Shipton et al, 2006;Childs et al, 2009;Faulkner et al, 2011a;Savage and Brodsky, 2011]. Damage zone thickness may also scale with parent fault length [Vermilye and Scholz, 1998;Davatzes and Aydin, 2003;de Joussineau et al, 2007;Perrin et al, 2016].…”
Section: Introductionmentioning
confidence: 98%
“…The depths to the top of the hard limestone or to the base of the previous units were ranged from 140 to 220 m. We recorded at several wells the water level raised, in maximum, to ~25 m over the main depth to groundwater. The pumping tests reflected that the fracture density, shale content, and thickness of rock units such as the shale, shaly limestone, and limy shale, which have low-to-medium effective zones (connected fractures) and affect directly on the rate of pumping or productivity of groundwater, and pure limestone, locations of wells according to the location of recorded faults and its down-throw and up-throw, and rate of pumping in governing the storages and transmissivity of the recorded aquifer Shipton et al (2006) concluded that the fault zones in the upper crust produce permeability heterogeneities that have a large impact on subsurface fluid migration and storage patterns.…”
Section: Well Datamentioning
confidence: 99%
“…A long-lived history of progressive deformation can be expected to lead to a more complex buildup of faults with potentially asymmetric permeability structures (Wibberley and Shimamoto 2003). Fault-zone thickness shows a clear positive correlation with displacement (Bense et al 2013;Childs et al 2009) but is strongly depending on the overall deformation history (Savage and Brodsky 2011;Shipton et al 2006 and references cited there).…”
Section: Introductionmentioning
confidence: 99%
“…Agosta et al 2010Agosta et al , 2012Caine et al 1996;Faulkner et al 2010;Jourde et al 2002;Mitchell and Faulkner 2012;Shipton and Cowie 2003;Shipton et al 2006;Wibberley and Shimamoto 2003;Wibberley et al 2008). In shallow crustal depths, primary deformation mechanisms such as cataclasis, deformation banding, brecciation and fracturing are similar for crystalline, siliciclastic and carbonate rocks, but water-rock interaction in carbonates has the potential to generate completely different permeability characteristics impacting fluid flow in aquifers (e.g.…”
Section: Introductionmentioning
confidence: 99%